2010
DOI: 10.1039/c0em00221f
|View full text |Cite
|
Sign up to set email alerts
|

Chemical monitoring of river water bodies in an EU outermost region: examples from the Azores archipelago (Portugal)

Abstract: Chemical monitoring of water quality on a total of 16 rivers in the Azores archipelago (Portugal), since 2003, made it possible to identify the major pressures and spatial geochemical variations along main course of the rivers. River water pollution is to a large extent associated to point sources, namely domestic wastewater discharges, especially in urban areas, and diffuse sources, associated with pasture land, and explain the high values on BOD(5) and nutrients (P and N). Heavy metals and metalloids, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…Previous research on river water chemistry in the archipelago has shown that the higher NO 3 contents are associated to areas where pasture lands are dominant [54], and despite the contribution of urban wastewater point sources, agriculture non-point sources are also critical for surface water pollution [42].…”
Section: Nitrates Occurrence and Fluxesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research on river water chemistry in the archipelago has shown that the higher NO 3 contents are associated to areas where pasture lands are dominant [54], and despite the contribution of urban wastewater point sources, agriculture non-point sources are also critical for surface water pollution [42].…”
Section: Nitrates Occurrence and Fluxesmentioning
confidence: 99%
“…In order to compare the groundwater results, the NO 3 surface water flux to the coastal water bodies was also estimated from the total runoff computed for the several islands [45] times the mean river water composition data described in [42]. In islands such as Santa Maria, São Miguel, Faial and Flores, the mean nitrate content for each watershed delimited as surface water bodies according the EU Water Framework Directive corresponds to the monitoring data in the river mouth, while the content for the entire island corresponds to the mean value that is determined with measurements made in the several watersheds.…”
Section: Nitrates Occurrence and Fluxesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Council Directive 2008/105/EC of 16 December 2008 established environmental quality standards in the field of water policy and management. This directive has been introduced to protect and achieve sustainable development water resource systems in the European Union countries (Cruz et al [3]). It establishes annual averages and maximum allowable concentrations (environmental quality standards) for priority substances and pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…The Water Framework Directive (WFD) was introduced to achieve protection and sustainable development of water resources in the European Union (EU) countries [1]. Subsequently the EU established Environmental Quality Standards (EQS) for 33 priority substances and other certain pollutants [2].…”
Section: Introductionmentioning
confidence: 99%